Development of Pancasila and Citizens Animation Video Learning Media-Based Powtoon - Nuraini Nuraini; Herlina Usman; Juhana Sakmal (ILIN Institute Makassar, 2023)
This research aims to develop learning media for Pancasila Education and Citizenship Education video animation based on Powtoon in elementary schools. This study uses the Research and Development development research method using the ADDIE approach (Analyze, Design, Develop, Implement, and Evaluate). This research was conducted at the Kelapa Dua Wetan 01 State Elementary School, East Jakarta. The research subjects of the third-grade elementary school students were twenty students. Data analysis techniques used interviews and questionnaires. The results of the development trial were evaluated by media experts 93.62%, material experts 89.29%, and linguists 95.13%, so an average score of 92.68% was obtained in the excellent category. This study indicates that Powtoon animation videos are appropriate for learning media to support Pancasila and Citizenship Education learning material on ethnic and cultural diversity in third-grade elementary schools in Indonesia.